THE METHYLATION OF TRANSFER RIBONUCLEIC ACID DURING REGENERATION OF THE LIVER - Tidwell, T. (The Rockefeller University Press, 1970)
Transfer ribonucleic acid(1) is methylated after the molecule is synthesized; at least eight enzymes are involved in the transfer of methyl groups (derived from methionine). The time courses of methylation and synthesis of tRNA during rat liver regeneration have been compared in an in vivo radioisotopic study, using 6-orotic acid-(14)C and (3)H-methyl-L-methionine as precursors in double label pulses. Liver regeneration is a synchronized system in which biochemical events of the cell cycle are separable. Transfer RNA methylation increase precedes by several hours tRNA synthesis during regeneration, although the curves overlap. A ratio of the relative rate of methylation to the relative rate of synthesis has been made; that curve positively correlates with the rise and fall of protein synthesis during regeneration. It is clear that methylation and synthesis of tRNA are only weakly coupled; changing methyl content of the tRNA "pool" resulting from differential tRNA methylase and polymerase activities may regulate the rate of protein synthesis in the cell cycle at the translational level. The "pool sizes" of uridine monophosphate (UMP) and S-adenosylmethionine (SAM) were measured indirectly; UMP and SAM were isolated from perchloric acid supernatants and their specific activities were computed. Differential changes in radioactivity available to tRNA methylases and polymerases are not a source of artifact. That is, the control of both the synthesis and methylation of tRNA is at the enzyme level in vivo, rather than at some enzymatic step prior to those enzymatic reactions.